Some invariant theorems on geometry of Einstein non-symmetric field theory - Liu Shu-Lin; Xu Sen-Lin (International Journal of Mathematics and Mathematical Sciences)
This paper generalizes Einstein's theorem. It is shown that under the transformation TΛ:Uikℓ→U¯ikℓ≡Uikℓ+δiℓΛk−δkℓΛi, curvature tensor Skℓmi(U), Ricci tensor Sik(U), and scalar curvature S(U) are all invariant, where Λ=Λjdxj is a closed 1-differential form on an n-dimensional manifold M.